The effect of Lesson Study on the development of Reflection thinking among teachers in the Qassim region and its relationship to some variables - Al-Otaibi, Aloush Mudeaj Mohaf; Al-Tamimi, Ghada Nasser (Journal of Educational and Psychological Sciences, 2020)
The aim of the research is to discover the effect of Lesson Study on developing contemplative thinking among teachers in the Qassim region and its relationship to the variables of experience and educational stage, and to achieve the goal of the research, the descriptive approach was used, and the research sample consisted of (120) teachers, and the tool was represented in a scale of contemplative thinking, The research reached the following results: It was found that there were statistically significant differences in favor of the group participating in the Lesson Study, which represented (37) teachers, where the level of significance appeared at(α= 000) which is statistically significant, and the value of the effect size is high ((89. ), And through this, it was found that there were statistically significant differences in favor of the group participating in the lesson study, Evidence of the effect of using the independent variable (Lesson Study) in developing contemplative thinking among female teachers in the Qassim region. The results also showed that there are no statistically significant differences attributable to the variable of experience, as well as the absence of statistically significant differences attributable to the variable of the educational stage, and in light of These results were a set of recommendations, the most important of which are: The importance of supporting school-based professional development through lesson study, and its adoption as one of the professional development methods that develop contemplative thinking for teachers.
Keywords: Lesson Study; Reflection thinking; Parameters of the Qassim region